A study of stone carving workers in Tang Dynasty – taking Shao Jianhe and Shao Jianchu as examples - Liu, Yuhan (Pacific International Journal, 2024)
The Tang Dynasty was a period of extreme prosperity of stone carving culture in Chinese history. In this period, stone carving was rich in content and huge in volume, and a large number of classic stone inscription calligraphy works emerged. This paper first studies the background of the development of stone carving in the Tang Dynasty and the general situation of the carving groups in the Tang Dynasty, then further explores the carving business of Shao’s family, and finally analyzes the relationship between calligraphers and carving workers by taking the Shao Brothers and Liu Gongquan as examples. This paper aims to further enhance the status of this group in the history of Chinese calligraphy through the analysis and study of the individual cases of the Tang Dynasty carving group, and affirm the contribution of this group in the history of Chinese calligraphy.